An unusual native tricuspid valve endocarditis caused by Candida colliculosa - DURMUŞOĞLU, LÜTFİYE; KORTEN, VOLKAN (BLACKWELL PUBLISHING LTD, 2003)
Candida colliculosa , which grew in blood cultures of a 71-year-old retired man with fever of unknown origin that had lasted for 7 months, in conjunction with transthoracic echocardiography, demonstrating a 20-mm vegetation, superior to the tricuspid valve, herniating into the right atrial cavity. The finding led to the diagnosis of fungal endocarditis. Fluconazole, 600 mg daily, was commenced for 8 days; followed by amphotericin B, 1 mg/kg daily. On the fourth day of the amphotericin B treatment, the patient underwent replacement of the infected tricuspid valve. Even though the initial postoperative period was relatively uncomplicated, the patient died after a gross aspiration on the 67th day of his hospital stay, despite aggressive cardiovascular support and antimicrobial therapy. This is the first report of a native tricuspid valve fungal endocarditis due to C. colliculosa or Torulaspora delbrueckii , which is not known to be a human pathogen.
Keywords: Candida spp.; fungal endocarditis; native-valve endocarditis; FUNGAL ENDOCARDITIS; YEASTS